Pengaruh Efikasi Diri terhadap Prestasi Belajar Mahasiswa Pascasarjana Prodi PAI STAIN Kediri dengan Motivasi sebagai Variabel Intervening - Sufirmansyah, Sufirmansyah (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2015)
This study intends to examine the effect of self efficacy towards the achievementof postgraduate students with motivation as an intervening variable. This studyuses a quantitative approach with path analysis as the study design. The researchdata were collected through questionnaires and documentation. Respondentsconsisted of 53 postgraduate students: 25 people of 4th semester and 28 peopleof 2th semester. Data analysis begins with the test of validity and reliabilityof the instrument. The assumption test was conducted of multicollinearity,autocorrelation, heteroscedasticity and normality, then proceed with pathanalysis. Results of the study revealed that: Self Efficacy influenced the motivationof Postgraduate STAIN Kediri students by 50.2%; Motivation had an effect onachievement of Postgraduate STAIN Kediri students by 29.9%; Self efficacyaffected on Postgraduate STAIN Kediri student’s achievement by 67.4%; andSelf efficacy influenced the achievement of Postgraduate STAIN Kediri studentsthrough motivation as an intervening variable by 82.4%, and the remaining17.6% influenced by other factors outside the model.